Three-Parameter Optimization of an Axially Loaded Beam on a Foundation - FORYŚ, A. S.; FORYŚ, A. (Engineering Transactions, 2007)
A beam of circular cross-section, made of viscoelastic material of Kelvin–Voigt type, is considered. The beam is symmetric with respect to its center, the length and volume of the beam are fixed and its ends are simply supported. The radius of the cross-section is a cubic function of co-ordinate. The beam interacts with a foundation of Winkler, Pasternak or Hetényi type and is axially loaded by a non-conservative force P(t) = P0 + P1 cos #t. Only the first instability region is taken into account. The shape of the beam is optimal if the critical value of P1 is maximal. A few numerical examples are presented on graphs.